Photosynthetic Light Reactions in Chemically Fixed Spinach Thylakoids - Hallier, U. W. (1969)
After proper fixation with glutaraldehyde, spinach thylakoids retain both photosystem I and photosystem II activity. The photochemical activity of fixed thylakoids is highly resistant to 1% triton. This indicates that fixed thylakoids may be useful starting material for isolation of functional components which can be related to the original structure of the membrane.